The Promotional Strategy of Srisasanti Gallery for the Addy Debil Exhibition "Feeling Fluorescent" Conducted in Collaboration with the Museum of Toys in Yogyakarta - Anisa Rahmadhani HRP; Muhammad Kholid Arif Rozaq; Raden Rara Vegasari Adya Ratna (TUMATA: Journal of Arts and Cultural Management, 2024)
The influence of digitalization has expanded the dissemination of art information through social media platforms such as TikTok and Instagram. This enables more effective and widespread promotion of art exhibitions. Therefore, Srisasanti Gallery has adopted various promotional strategies, including collaborations with other institutions such as the Museum of Toys, to increase visitor enthusiasm for art exhibitions, as exemplified by the "Feeling Fluorescent" exhibition by Addy Debil. This research utilized a descriptive qualitative method with a case study approach. Data were collected through participatory observation, semi-structured interviews, and documentation. The research findings reveal that Srisasanti Gallery implemented a promotional strategy (Mahmud Machfoedz, 2010: 3-16) by segmenting the target audience, sending invitations, compiling a list of content creators, media placement, distributing exhibition posters, designing content, and planning a promotional timeline. Additionally, other promotional mix elements (Hamdani, 2006 in Sunyoto, 2015: 160-161) such as advertising, personal selling, public relations, word of mouth, and direct marketing were also effectively utilized by Srisasanti Gallery. The involvement of content creators in disseminating information about the exhibition on social media platforms like TikTok and Instagram also had a significant impact in attracting a large number of visitors. The promotional strategy developed by Srisasanti Gallery not only succeeded in making the exhibition go viral on social media but also yielded positive results in terms of visitor numbers, reaching 6000 visitors during its month-long run. This success serves as evidence of the effectiveness of the promotional strategies implemented by this gallery, which may potentially serve as a model for promoting future cultural art events.